The Politics of White Rights : Race, Justice, and Integrating Alabama's Schools - Bagley, Joseph, 1981- (Book collections on Project MUSE., 2018)
"In this narrative account of school desegregation in Alabama, I uncover critical changes in segregationist strategy which allowed whites to engage in a long resistance movement, well after most historians consider 'massive resistance' to have ended. Using a malleable language of 'law and order' in their efforts to thwart desegregation litigation--including the landmark Lee v. Macon County Board of Education case--whites learned to protect what rights and privilege they could by crafting superficially race-neutral legislation designed to withstand court scrutiny. Scholars have explained how whites framed their flight to suburbs and private schools as protecting their right to associate with those of their own choosing, but I reveal here an even more damaging and enduring fight to protect white money. Using the lessons learned in the school desegregation battle, legislators in Alabama in the 1970s erected barriers to white taxation that continue to cripple public education in heavily black areas. And they have, more recently, achieved their longtime goal of funding racially exclusive private schools. In ongoing litigation, politicians who enacted these laws, and white communities which continue to secede from county school systems, insist that their motivations have nothing to do with race. Those who read this book will know better"--